High-precision radiocarbon age calibration for terrestrial and marine samples - Stuiver, M.; Reimer, P. J.; Braziunas, T. F. (Radiocarbon, 1998)
Single-year and decadal radiocarbon tree-ring ages are tabulated and discussed in terms of C-14 age calibration. The single-year data form the basis of a detailed 14C age calibration curve for the cal AD 1510-1954 interval ("cal" denotes calibrated). The Seattle decadal data set (back to 11,617 cal sp, with 0 sp = AD 1950) is a component of the integrated decadal INTCAL98 C-14 age curve (Stuiver et al. 1998). Atmospheric C-14 ages can be transformed into C-14 ages of the global ocean using a carbon reservoir model. INTCAL98 C-14 ages, used for these calculations, yield global ocean C-14 ages differing slightly from previously published ones (Stuiver and Braziunas 1993b). We include discussions of offsets, error multipliers, regional C-14 age differences and marine C-14 age response to oceanic and atmospheric forcing.
155qrTimes Cited:705 Cited References Count:31
Keywords: ad 1950-500 bc; c-14 data; decadal calibration; reservoir ages; time scale